2015
DOI: 10.4102/phcfm.v7i1.753
|View full text |Cite
|
Sign up to set email alerts
|

Auditing chronic disease care: Does it make a difference?

Abstract: BackgroundAn integrated audit tool was developed for five chronic diseases, namely diabetes, hypertension, asthma, chronic obstructive pulmonary disease and epilepsy. Annual audits have been done in the Western Cape Metro district since 2009. The year 2012 was the first year that all six districts in South Africa's Western Cape Province participated in the audit process.AimTo determine whether clinical audits improve chronic disease care in health districts over time.SettingWestern Cape Province, South Africa.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…These factors have been reported by patients and health-care providers alike to be significant sources of frustration and to have a negative impact on the quality of NCD care. 26,27,28…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors have been reported by patients and health-care providers alike to be significant sources of frustration and to have a negative impact on the quality of NCD care. 26,27,28…”
Section: Discussionmentioning
confidence: 99%
“…This opinion is borne out by an evaluation conducted by Essel et al 27 which showed that in districts where audits had been conducted for a period of time, there were marked improvements in clinical processes compared to districts that had only recently begun doing audits. 23…”
Section: Theme 2: National Government Action To Address Diabetes and mentioning
confidence: 99%
“…Diabetes self-management education complements diabetes medication, which has failed to control blood glucose despite its accessibility and proven efficacy in many type 2 diabetic patients (HBA1c ≤ 6.5%). An estimated 80% of type 2 diabetes patients in Kenya 5 and Cape Town, South Africa, respectively 6 have poor glycaemic control contributing to an increase in diabetes complications. This increase necessitates effective diabetes prevention and control measures including DSME, especially noting that a 1-point improvement of HbA1c is associated with a 20% and 30% – 40% decrease in macro-vascular and micro-vascular complications, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…44 45 Such a system can support effective auditing, which can improve care processes in health districts over the long term. 45 …”
Section: Methodsmentioning
confidence: 99%